KOMODITAS UNGGULAN DAN POTENSI DAYA SAING SEKTOR PERTANIAN KABUPATEN PADANG PARIAMAN - Nuraini Nuraini; Syahrial Syahrial; Angelia Leovita (JURNAL AGRIBISNIS TERPADU, 2023)
The agricultural sector is the second largest contributor to the PDRB of Padang Pariaman Regency, therefore Padang Regency has great potential to improve the economy of the agricultural sector. This study aims to 1) analyze the main commodities on the basis 2) analyze the economic competitiveness of the agricultural sector in Padang Pariaman Regency and 3) analyze the trends of the leading commodities in the future. The analytical tools used are location quantient, localization quotient, specialization quotient, shift share and dynamic location quantient. The results showed 1) Padang Pariaman Regency had 43 percent of the 14 commodity base commodities, 2) the food crops, horticulture, and plantation sub-sectors had competitiveness with increased growth, and 3) there were 50 percent of the 14 agricultural sector base commodities that were future trends. District governments Padang Pariaman need to make policies that can support increased activity in the agricultural sector, improve technology and innovation so that productivity increases.